Polar Stratospheric Clouds: Satellite Observations, Processes, and Role in Ozone Depletion. (10th June 2021) - Tritscher, Ines; Pitts, Michael C.; Poole, Lamont R.; Alexander, Simon P.; Cairo, Francesco; Chipperfield, Martyn P.; Grooß, Jens‐Uwe; Höpfner, Michael; Lambert, Alyn; Luo, Beiping; Molleker, Sergey; Orr, Andrew; et al.
Abstract: Polar stratospheric clouds (PSCs) play important roles in stratospheric ozone depletion during winter and spring at high latitudes (e.g., the Antarctic ozone hole). PSC particles provide sites for heterogeneous reactions that convert stable chlorine reservoir species to radicals that destroy ozone catalytically. PSCs also prolong ozone depletion by delaying chlorine deactivation through the removal of gas‐phase HNO3 and H2 O by sedimentation of large nitric acid trihydrate (NAT) and ice particles. Contemporary observations by the spaceborne instruments Michelson Interferometer for Passive Atmospheric Sounding (MIPAS), Microwave Limb Sounder (MLS), and Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) have provided an unprecedented polar vortex‐wide climatological view of PSC occurrence and composition in both hemispheres. These data have spurred advances in our understanding of PSC formation and related dynamical processes, especially the firm evidence of widespread heterogeneous nucleation of both NAT and ice PSC particles, perhaps on nuclei of meteoritic origin. Heterogeneous chlorine activation appears to be well understood. Reaction coefficients on/in liquid droplets have been measured accurately, and while uncertainties remain for reactions on solid NAT and ice particles, they are considered relatively unimportant since under most conditions chlorine activation occurs on/in liquid droplets. There have been notable advances in the ability of chemical transport and chemistry‐climate models to reproduce PSC temporal/spatial distributions and composition observed from space. Continued spaceborne PSC observations will facilitate further improvements in the representation of PSC processes in global models and enable more accurate projections of the evolution of polar ozone and the global ozone layer as climate changes. Plain Language Summary: Polar stratospheric clouds (PSCs) occur during winter and early spring in the polar stratosphere, when temperatures are low enough to enable cloud formation despite the extremely dry conditions. Ground‐based PSC sightings date back to the late 19th century, but they were little more than a scientific curiosity until the discovery of the Antarctic ozone hole in 1985. Soon thereafter, it was shown that PSCs play a crucial role in converting stable halogen (mainly chlorine) species of anthropogenic origin into reactive gases that rapidly destroy ozone. Considerable progress was made over the next two decades in quantifying these processes through laboratory studies, field campaigns, and limited spaceborne observations. We are now reaping the benefits of new PSC observations over the entire polar regions from three complementary 21st century spaceborne instruments. This study reviews these instruments and highlights new findings on PSC occurrence and composition. These datasets have also triggered advances in understanding how PSCs form and the influence of atmospheric dynamics, as well as improvements in how detailed cloud processes are approximated in global models. This will ultimately lead to better predictions of how quickly the stratospheric ozone layer will recover from human influence as global climate changes in the future. Key Points: We provide a new vortex‐wide climatology of polar stratospheric cloud occurrence and composition based on 21st century satellite data We review advances in understanding cloud formation, the role of dynamical processes, and heterogeneous chlorine activation We highlight improvements in techniques for parameterizing polar stratospheric clouds and their effects in global models